Determinan terhadap Pendeteksi Tindakan Fraud dengan Corporate Culture sebagai Pemoderasi (Studi Kasus pada PLN ULP Bangli) : (Studi Kasus pada PLN ULP Bangli) - intan handayani; Made Arie Wahyuni (Universitas Pendidikan Ganesha, 2023)
This research was conducted to examine the effect of ethical behavior, Machiavellian, and the effectiveness of the whistleblowing system on fraud detection with corporate culture as a moderation at PLN ULP Bangli. This study uses a quantitative approach. The population in this study were all PLN ULP Bangli employees, namely 114 employees. This research sample determined by purposive sampling technique. Therefore, the sample used was 98 employees. Data was collected using a questionnaire with the scale used, namely the Likert scale. Then the data were analyzed with several analyzes in the SPSS 26 program, and moderating variable interaction test. The results showed that ethical behavior, Machiavellian and effectiveness of the whistleblowing system have a positive and significant effect on fraud prevention, and ethical behavior, Machiavellian and effectiveness of the whistleblowing system have a positive and significant effect on fraud prevention with corporate culture as a moderator.